2023
DOI: 10.3390/ijms24065899
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of the Cytochrome P450 Gene Family in Bemisia tabaci MED and Their Roles in the Insecticide Resistance

Abstract: The whitefly, Bemisia tabaci MED (Hemiptera: Aleyrodidae), is an omnivorous agricultural pest, which causes huge economic losses to agriculture and is highly resistant to many pesticides. The overexpression of cytochrome P450 may play an important role in host adaptation and insecticide resistance in B. tabaci MED. Therefore, the present study systematically analyzed the cytochrome P450 gene family at the genome-wide level to understand its function in B. tabaci MED. Our analysis identified 58 cytochrome P450 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Of all the DbP450s, CYPs in the families of CYP4 and CYP6 accounted for more than half the identified P450s in D. baibarana. Cytochrome P450s from the CYP4 and CYP6 families have been reported to be associated with pesticide resistance and host adaptation [19]. Therefore, it is speculated that the apparent CYP expansion in these two families may facilitate the survival of the tea black tussock moth in the tea plantations.…”
Section: Discussionmentioning
confidence: 99%
“…Of all the DbP450s, CYPs in the families of CYP4 and CYP6 accounted for more than half the identified P450s in D. baibarana. Cytochrome P450s from the CYP4 and CYP6 families have been reported to be associated with pesticide resistance and host adaptation [19]. Therefore, it is speculated that the apparent CYP expansion in these two families may facilitate the survival of the tea black tussock moth in the tea plantations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to detoxifying exogenous toxic compounds like insecticides and plant secondary insecticides, cytochrome P450s play a role in the synthesis and degradation of endogenous compounds in insects, including hormones and sex pheromones. They also mediate insect growth and development, host plant adaptation, and insecticide resistance [ 37 ]. To date, the CYP450 gene family has been identified and characterized in prokaryote (cyanobacteria) [ 38 ] and fungi [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…And the CYP450 gene family has also been analyzed in various plants species, such as rice [ 40 ], tomato [ 41 ], wheat [ 42 ], maize [ 42 ], sorghum [ 43 ], soybean [ 44 ], tea [ 45 ], and others. In insects, it was reported that the CYP450 gene family of Drosophila melanogaster [ 46 ], silkworm ( Bombyx mori ) [ 47 ], Plutella xylostella [ 48 ], Scopula subpunctaria [ 49 ], cotton leafhopper ( Amrasca biguttula ) [ 50 ], bees [ 51 ], and Bemisia tabaci [ 37 ] have been identified and analyzed. However, several aphid species had not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that insecticide resistance is often conferred by cytochrome p450 monooxygenases [ 32 ]. For instance, CYP4 and CYP6 families are associated with imidacloprid tolerance in B. tabaci MED [ 33 ], while the CYP6DB3 gene was also over-expressed in thiamethoxam-resistant B. tabaci populations and the expression of CYP6DB3 can be induced under thiamethoxam selection pressure [ 34 ]. Furthermore, the P450 monooxygenase was found to be conducive to the development of abamectin resistance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%